(untitled) (Portuguese Journal of Family Medicine and General Practice, 2023)
Introduction: Herpes zoster (HZ) is a disease that results from the reactivation of the varicella-zoster virus (VZV). Typically, it manifests as a painful vesicular rash that follows the distribution of a dermatome. However, there are other, less frequent, ways in which HZ manifests itself in several dermatomes, such as HZ multi-dermatomal. Case description: We report to a 72-year-old female patient who presented with complaints of left hemicranial and mandibular pain, associated with erythematous areas scattered over the scalp of the left hemicranium, on the helix of the left ear with millimeter vesicles and a small erythematous lesion on the left mandibular region with an outline of vesicles. She was medicated with valacyclovir 1000mg weekly, progressively improving the pain and rash complaints. Commentary: The classic HZ of thoracic dermatomes is the most frequently described in the literature. There are several case reports of multi-dermatomal HZ, affecting mainly the head and neck, and mechanisms have already been proposed that may explain the greater propensity of the VZV to spread through several linked dermatomes. Although less frequent, it is important to know this atypical manifestation of HZ, to allow early diagnosis and treatment.